“I Know Down to My Ribs”: A Study of the Embodied Adult Learning of Creative Writers - Jennifer Tobin; Elizabeth J. Tisdell (Adult Education Research Conference, 2014)
This paper reports a narrative analysis on the embodied learning of creative writers, by providing an extended narrative on the embodied learning of one participant. It is theoretically grounded in Merleau-Ponty’s philosophy of the body, Gendlin’s notion of the “felt sense, and Jordi’s analysis of reflection for integrating mind and body.